The Caucasus department of the Russian Technical Society as the technical thought centre of southern Caucasian region - Hurinchuk, S. V. (History of science and technology, 2017)
The article analyzes and summarizes the role of the Russian Technical Society’s Caucasus department in spreading technical thought in the late XIX th - early XX th century in the Caucasus. Relying on experience and achievements of national science and technology author has all the grounds to assert that rapid development of native industries and national economy in the period of capitalist development in the Russian Empire led to the scientific information accumulation and the necessity of its concentration around certain centers. Under such conditions the creation of the technical periodicals of the Russian Technical Society’s Caucasus department was dictated by the requirementss of the Caucasus region, which acutely needed a quick and competent solution of technological problems in upbringing scientific and technical personnel.